Factors associated with the functional outcome of patients with ischemic stroke treated with intravenous thrombolysis in a Peruvian hospital. - Gallo-Guerrero, Marla L. (2020)
Objective: To describe the treatment of acute ischemic strokes with intravenous rtPA and determine the factors associated with the functional outcomes of patients treated with thrombolysis in a Peruvian hospital. Material and Methods: A prospective, longitudinal cohort study of patients with ischemic stroke who received rtPA over a period of 3 years was performed. The association of demographic and clinical data with functional status was assessed 3 months after the intervention. Simple and multivariate Poisson regression models were performed to evaluate associations with functional prognosis, and Relative Risk (RR) with a 95% confidence interval (CI) was used as a measure of association. Results: During the study period, 74 patients (1.19% of the total) received IV thrombolysis, and 68.18% of them achieved functional independence (mRS 0-2) at 90 days. We found a mortality of 6%, an intracerebral hemorrhage (ICH) rate of 3%. Glycemia >140 mg/dl (OR 5.12; 1.31-20.02; p = 0.019), and posterior circulation infarcts (OR 7.47; 1.01-55.15; p = 0,04) were associated with an increased risk of functional dependency. Conclusions: In the studied cohort, most of the patients who underwent thrombolytic therapy achieved a functional independence at 3 months. Hyperglycemia (>140gr/dl) and vertebro-basilar infarcts were associated with an increased risk of functional dependence